Development of a Real-Time, Large Area, High Spatial Resolution Particle Tracker Based on Scintillating Fibers - D. Lo Presti; D. L. Bonanno; F. Longhitano; C. Pugliatti; S. Aiello; G. A. P. Cirrone; V. Giordano; E. Leonora; N. Randazzo; S. Reito; F. Romano; G. V. Russo; et al. (Advances in High Energy Physics)
The design of a detector for tracking charged particles is presented together with the characterization techniques developed to extract the main design specifications. The goals for the final detector are to achieve real-time imaging performances, a large detection area, and a high spatial resolution, particularly suitable for medical imaging applications. This paper describes the prototype of the tracker plane, which has a 20 × 20 cm2 sensitive area consisting of two crossed ribbons of 500 μm square scintillating fibers. The information about the hit position extracted real-time tracker in an innovative way, using a reduced number of the read-out channels to obtain a very large detection area but with moderate costs and complexity. The performances of the tracker have been investigated using β sources, cosmic rays, and a 62 MeV proton beam.